Neo-Sinkretisme Petani Muhammadiyah - Abdul Munir Mulkhan (Al-Jami'ah: Journal of Islamic Studies, 1996)
Syncretism is a belief that grows among rural peasants. The growth of the belief is closely related to their social and economies status for this reason Muhammadiyah, as an Islamic purifying organization, is not well accepted by them. social changes in which the number of populations increases and the farm-land and shelter decreases. has fostered rationalization of myths and supernatural belief. since then, Muhammadiyah is gradually accepted by rural peasants. In essence, the synergetic belief of the peasants is not in accordance with Muhammadiyah principles. Even though, the data show an increasing number of rural peasants who commit to this organization. This commitment means distortion of functional relationship patten between work and belief. Being Muhammadiyah followers can being contradiction to their previous belief and their life patten. Sueh kind of internal contradiction raises a conflict of belief which leads to the rise of new syncretism. In a new form the meaning and function of syncretism and Muhammadiyah movement changed on the bases of their cultural system. This fact shows belief dualism among rural peasants. Muhammadiyah has a mission of eradicating syncretism which has been the basis of rural peasants' view. The commitment of the peasants to follow this organization does not mean rejection of this belief. Rather, life patten and the struggle of fulfilling their daily needs make them choose both, organization and belief. which give rise to new syncretism. Economies and political crisis urges the peasants to take Muhammadiyah as their new identity which will bring up their position in the changing social structure. consequently, the function of the organization changes into more or less, a mediator in facing social, economies and political structure which is bigger and modern. on one hand, to make them accepted by Muhammadiyah community, their syncretic belief and its ritual systems are modified. And on the other hand, some of Muhammadiyah institution components are sacralized according to their way of life. Sueh a condition could bring a charismatic experience, ln which Muhammadiyah commitment of peasants is stronger than that of other followers.